The Economic Reports of the President and the Problem of Inflation - Fetter, Frank Whitson (Quarterly Journal of Economics, 1949)
Journal Article The Economic Reports of the President and the Problem of Inflation Get access Frank Whitson Fetter Frank Whitson Fetter Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 63, Issue 2, May 1949, Pages 273–281, https://doi.org/10.2307/1883102 Published: 01 May 1949